Characteristics and optimal ablation settings of a novel, contact‐force sensing and local impedance‐enabled catheter in an ex vivo perfused swine ventricle model. (30th September 2021) - Tsutsui, Kenta; Kawano, Daisuke; Mori, Hitoshi; Kato, Ritsushi; Ikeda, Yoshifumi; Sumitomo, Naokata; Fukaya, Hidehira; Iwanaga, Shiro; Nakano, Shintaro; Muramatsu, Toshihiro; Matsumoto, Kazuo
Abstract: Background: Local impedance (LI) has emerged as a new technology that informs on electrical catheter‐tissue coupling during radiofrequency (RF) ablation. Recently, IntellaNav StablePoint, a novel LI‐enabled catheter that equips contact force (CF) sensing, has been introduced. Although StablePoint and its predecessor IntellaNav MiFi OI share the common technology that reports LI, distinct mechanics for LI sensing between the two products raise a concern that the LI‐RF lesion formation relationship may differ. Methods: In an ex vivo swine cardiac tissue model, we investigated the initial level and range of a reduction in LI during a 60‐s RF ablation and the resultant lesion characteristics at nine combinations of three energy power (30, 40, and 50 W) and CF (10, 30, and 50 g) steps. Correlations and interactions between CF, LI, wattage, and formed lesions were analyzed. Incidence of achieving LI drop plateau and that of a steam pop were also determined. Results: Positive correlations existed between CF and initial LI, CF and absolute/relative LI drop, CF and lesion volume, and LI drop and lesion volume. At the same LI drop, wattage‐dependent gain in lesion volume was observed. Steam pops occurred in all CF steps and the prevalence was highest at 50 W. LI drop predicted a steam pop with a cutoff value at 89Ω. Conclusion: In StablePoint, wattage crucially affects LI drop and lesion volume. Because 30 W ablation may by underpowered for intramural lesion formation and 50 W often resulted in a steam pop, 40 W appears to achieve the balance between the safety and efficacy.